Quality of Nursing Services Affect the Patient Satisfaction in Hospital - Rista Apriana; Ida Ratnasari (JOURNAL OF NONCOMMUNICABLE DISEASES, 2021)
Improved quality of services was needed to provide patient satisfaction. Quality of nursing care consists of five dimensions these are responsiveness, assurance, tangibles, emphaty, and reliability. The aimed of this study was determined the relationship of nursing care quality with patient satisfaction level in hospital. The type of this research was non-experiment research and used cross sectional design. This research used  purposive sampling technique, with the total sample were 98 patients in Hospital. The data was collected using questionnaire and analyzed using pearson product moment test. The average quality of nursing services was at score 77.36, with the standard deviation at 8.91. The average patient satisfaction was at score 101.59, with the standard deviation at the score of 11.60. The result of Pearson Product Moment statistic test showed that there was a significant and positive correlation between the quality of nursing services with the level of patient satisfaction with the strong relationship correlation proved with p-value = 0,000 and r-value= 0,592. It showed that increasing the quality of nursing services given to the patient can increased the level of patient satisfaction.